Cdc42 regulates migration, invadopodia formatio and invasion in glioblastoma cells. (c2018) - Masri, Zeinab S El (2018)
Glioblastoma multiforme (GBM) is one of the most aggressive human cancers. It’s associated with poor prognosis and high mortality rate. Migration and invasion of glioblastoma multiforme into critical areas of the brain is considered the main reason behind treatment failure. The process of cellular migration is a multistep process requiring a dynamic regulation of the actin cytoskeleton. The Rho family of small GTPases play a central role in regulating cancer cell motility and invasion. Here we study the role of Cdc42, a member of the Rho family of small GTPases, in glioblastoma cell migration and invasion. We first wanted to determine the effect of Cdc42 on 2D motility in glioblastoma cells. Using siRNA against Cdc42 showed that Cdc42 positively regulates cell migration. We next wanted to see the mechanism by which Cdc42 regulates cell motility. Our data showed that Cdc42 decreases cell adhesion by downregulating RhoA and Rac1. Previous work from our laboratory correlated the persistent activation of RhoA through the knock down of StarD13 (a GAP for RhoA) with an inhibition of cell motility. This could be the mimicked here in the Cdc42 knock down phenotype and its effect on motility. We also investigated the role of Cdc42 in cell invasion. Our results showed that Cdc42 is essential for the formation of invadopodia, the actin rich structures necessary for the degradation of the extracellular matrix. Hence, Cdc42 might also enhance the invasiveness of glioblastoma cells.